Radiofrequency resonance heating near medical devices in magnetic resonance imaging. Issue 2 (21st December 2012) - Brown, James E.; Lee, Choon S.
Abstract Magnetic resonance imaging (MRI) is a desirable diagnostic modality because of its excellence soft‐tissue imaging capability. Patients with implanted medical devices are presently denied access to this modality due to adverse interaction of the device with the electromagnetic fields of the MRI system. These adverse interactions include heating near the tissue–electrode interface due to the radiofrequency (RF) field. The purpose of this work is to develop a basic model of the resonance to further explain the mechanism of RF heating in MRI near implanted medical devices. The work will concentrate on simplified structures that can be well understood from an analytical approach. The relationships shown in the simplification can then be extended to the more complex geometry of an implanted lead. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:299–302, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27332